PROSES KREATIF DALAM PEMBUATAN KONTEN PROMOSI DIGITAL PRODUK HERBAL JYB GROUP - Mevia, Nadia Arta; Suwanda, Bayu Suriaatmaja (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2025)
This research explores the creative process involved in developing digital promotional content for JYB Group's herbal products. Employing a descriptive qualitative approach, data were collected through interviews and observation. The findings reveal that the creative process is executed in a systematic and collaborative manner, shaped by both internal and external influencing factors. The construction of promotional messages places emphasis on relevance, credibility, and visual consistency. These results are in accordance with Wallas's theory of the creative process, which comprises the stages of preparation, incubation, illumination, and verification.